Application of Accounting Information System at Fahiluka Health Center - Arlin Prisilia Dredge; Mayang Sari Edastami (Komunitas Dosen Indonesia, 2022)
This study aims to find out how to prepare financial statements at the Fahiluka health center. This type of research uses a qualitative descriptive method with a case study approach in the form of financial statement data at the Fahiluka health center. The data sources used in this study are data obtained from an interview with one of the staff of the Fahiluka health center and books, official archives or forms of records related to the financial statements of the Fahiluka health center. and using data collection techniques in interviews and documentation. The results of this study show that the lack of training regarding the process of preparing public sector financial statements in accordance with applicable government regulations or accounting standards has resulted in the Fahiluka health center not implementing an accounting information system and the resulting financial statements are not in accordance with government regulations or government accounting standards. The preparation of financial statements at the Fahiluka health center is not someone who has expertise in the field of accounting (bookkeeping) and the financial statements are not only prepared by one person in charge or treasurer but are prepared by each person in charge of the activity program. The results of this study mean that the Fahiluka health center has not implemented an accounting information system where in the process of preparing financial statements is still manually using Microsoft excel, the stages of preparing financial statements at the Fahiluka health center are only recorded in the form of journals, then reporting in the form of financial statements so that the financial statement information produced is only in the form of a general cash book